Upaya Pengelolaan Sampah Anorganik Melalui Edukasi Kelas Hijau di Dusun 1 Desa Cisuren` - Suhendra; Azka Aulia Albani; Annisa Annafiah Ghudzamir; Alyvia Putri Annanto; Aisyah Alfiana Dewi (PELITA NUSA TENGGARA, 2026)
The issue of inorganic waste management remains an environmental concern that requires serious attention. Cisuren Village in Lebak Regency faces a lack of public awareness regarding waste sorting and recycling. The Green Class program was implemented in three elementary schools to improve students’ awareness and skills in managing inorganic waste. The activities included educational sessions, demonstrations, and recycling practices using a participatory approach. The results showed an increase in students’ understanding of waste types and their ability to recycle materials into useful products. Based on Bronfenbrenner’s Ecological Theory and Bandura’s Social Learning Theory, behavioral changes occurred through environmental interaction and the imitation of positive models. The Green Class program proved effective in fostering knowledge, attitudes, and environmentally responsible behavior among elementary school students.